Effect of dwarfism genes on some agronomic and morphological characteristics of Triticum aestivum (L.) Thell - Zanatta, Ana Christina Albuquerque; Oerlecke, Dênio (Pesquisa Agropecuaria Brasileira, 1991)
Four near-isogenic lines involving Rht1, Rht2, Rht1 + Rht2 and Rht8 dwarfing genes, with IAC 5-Maringá, a Brazilian wheat variety as the recurrent progenitor, as well as their tall sister lines, were grown under field conditions in Passo Fundo, RS, Brazil. Twenty-three agronomic and morphological characteristics were determined and analyzed. It was observed that Rht1, Rht2 and Rht8 had similar reduction effect on the plant height, as well as that Rht1 and Rht2 summed their effects on this characteristic. Rht1, Rht2 and Rht8 did not seem to affect the yield components evaluated, except the tillers number that increased when Rht8 was present in the genotype. It was also observed that these genes tended to introduce and/or to increase the desuniformity for some characteristics but, at the same time, they did not seem to affect other agronomic and morphological wheat traits.
Keywords: wheat; genes Rht1; Rht2; Rht8; yield components; morphological characteristics